Alzheimer's disease diagnosis based on detection of autoantibodies against Aβ using Aβ40 peptide in liposomes - Monteiro, Júlio César; Yokomichi, Anna Laura Yuri; de Carvalho Bovolato, Ana Lívia [UNESP]; Schelp, Arthur Oscar [UNESP]; Ribeiro, Sidney José Lima [UNESP]; Deffune, Elenice [UNESP]; Moraes, Marli Leite de (Elsevier, 2022)
Background: Alzheimer's disease (AD) is the most common form of dementia and affect more than 50 million people worldwide. Thus, there is a high demand by non-invasive methods for an early diagnosis. This work explores the AD diagnostic using the amyloid beta 1–40 (Aβ40) peptide encapsulated into dipalmitoyl phosphatidyl glycerol (DPPG) liposomes and immobilized on polyethylene imine previously deposited on screen-printed carbon electrodes to detect autoantibodies against Aβ40, a potential biomarker found in plasma samples. Methods: The immunosensor assembly was accompanied by atomic force microscopy (AFM) images that showed globular aggregates from 20 to 200 nm corresponding liposomes and by cyclic voltammetry (CV) through increase of the voltammogram area each material deposited. After building the immunosensor, when it was exposed to antibody anti-Aβ40, there was an increase in film roughness of approximately 9 nm, indicating the formation of the immunocomplex. Results: In the detection by CV, the presence of specific antibody, in the range of 0.1 to 10 μg/ml, resulted in an increase in the voltammograms area and current in 0.45 V reaching 3.2 µA.V and 5.7 μA, respectively, in comparison with the control system, which remained almost unchanged from 0.1 μg/ml. In patient samples, both cerebrospinal fluid (CSF) and plasma, was possible separated among positive and negative samples for AD using CV profile and area, with a difference of 0.1 μA.V from the upper error bar of healthy samples for CSF sample and 0.6 μA.V for plasma sample. Conclusions: These results showed the feasibility of the method employed for the non-invasive diagnostic of Alzheimer's disease detecting natural autoantibodies that circulate in plasma through a simple and easy-to-interpret method.
Keywords: Alzheimer's disease; Autoantibody; Cyclic voltammetry; Immunosensor; Layer-by-layer film; Liposomes; βA40